Case Report: Dupilumab therapy for immune checkpoint inhibitor-induced bullous pemphigoid enables dual immunotherapy initiation in progressive malignant melanoma - Grüninger, Janine; Lehr, Saskia; Meiss, Frank; Rafei, David; Schauer, Franziska (Frontiers in Oncology, 2025)
Immune checkpoint inhibitors (ICIs) targeting PD-1, PD-L1 and CTLA-4 have transformed the treatment of malignant melanoma, significantly improving patient survival rates. However, these therapies often result in immune-related adverse events, with cutaneous toxicities being the most prevalent. One such irAE is bullous pemphigoid (BP), which is rare but challenging, and is characterised by autoantibody-mediated blistering at the dermo-epidermal junction. ICI-induced bullous pemphigoid (irBP) affects around 0.6% of patients and presents a therapeutic challenge as it requires the management of both the autoimmune response and the underlying malignancy. Recent research has highlighted the role of Th2 cytokines, particularly interleukin-4 (IL-4) and IL-13, and eosinophils in the pathogenesis of BP and irBP. Dupilumab, a monoclonal antibody that targets the IL-4 receptor alpha subunit, inhibits IL-4 and IL-13 signalling. In this report, we present a case of irBP in a patient with metastatic melanoma who was successfully treated with Dupilumab. Following resolution of the autoimmune skin toxicity, the patient was re-challenged with dual ICI therapy (Nivolumab and Ipilimumab), which remains the recommended first-line treatment for metastatic melanoma. This case highlights the potential of Dupilumab as a steroid-sparing option in the management of irBP, enabling continued oncological treatment.